Co-Digestion of Napier Grass and Its Silage with Cow Dung for Bio-Hydrogen and Methane Production by Two-Stage Anaerobic Digestion Process - Wipa Prapinagsorn; Sureewan Sittijunda; Alissara Reungsang (Energies, 2017)
The objective of this study was to efficiently utilize the napier grass and its silage to produce bio-hydrogen and methane by a two-stage process in batch mode. First, the production of hydrogen from a co-digestion of grass with cow dung and silage with cow dung by Clostridium butyricum Thailand Institute of Scientific and Technological Research (TISTR) 1032 was conducted. The results indicated that bio-hydrogen production by C. butyricum TISTR 1032 gave a higher hydrogen yield (HY) than without C. butyricum addition. The HY of 6.98 and 27.71 mL H2/g-Volatile solidadded (VSadded), were obtained from a co-digestion of grass with cow dung and silage with cow dung by C. butyricum, respectively. The hydrogenic effluent and solid residue left over after hydrogen fermentation were further used as substrates for methane production (Batch I). Methane yield (MY) from hydrogenic effluent of grass with cow dung and silage with cow dung were 169.87 and 141.33 mL CH4/g-CODadded (COD: chemical oxygen demand), respectively. The maximum MY of 210.10 and 177.79 mL CH4/g-VSadded, respectively, were attained from solid residues left over after bio-hydrogen production pretreated by enzyme (cellulase cocktail) and alkali (NaOH). Afterward, solid residue left over after methane production (Batch I) was used as the substrate for methane production (Batch II). A maximum MY of 370.39 and 370.99 mL CH4/g-VSadded were achieved from solid residue repeatedly pretreated by alkaline plus enzyme, respectively. The overall energy yield in the two-stage bio-hydrogen and methane production process was derived from a bio-hydrogen production, a methane production from hydrogenic effluent, methane production of pretreated solid residue (Batch I) and methane production of repeatedly pretreated solid residue (Batch II), which yielded 480.27 and 204.70 MJ/g-VSadded, respectively.